PENGARUH KEPEMIMPINAN GURU DAN KEMAMPUAN BERKOMUNIKASI GURU TERHADAP MOTIVASI BELAJAR EKONOMI SISWA KELAS XI DI SMA NEGERI 3 PEMATANGSIANTAR T.A. 2024/2025 - Januarius Cesar Parasian Napitu; Herlina Hotmadinar Sianipar; Paulina Herlina N Sirait (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to determine whether there is an influence of teacher leadership and teacher communication skills on the motivation to learn economics of class XI students at SMA Negeri 3 Pematangsiantar. The variables in this study are teacher leadership and teacher communication skills as independent variables and student motivation to learn economics as the dependent variable. This type of research is quantitative research with a population of class XI of 113 students and a research sample of 88 students. Data collection techniques were carried out by observation and distributing questionnaires, while data analysis techniques used validity tests, reliability tests, normality tests, multiple linear regression tests, t tests, f tests and determination coefficient tests.Based on the results of data analysis using excel, it states that there is a significant influence between teacher leadership on the motivation to learn economics of class XI students of SMA Negeri 3 Pematangsiantar, seen from the Tcount value of 65.26> Ttable 1.662. Then, there is a significant influence between teacher communication skills on the motivation to learn economics of class XI students of SMA Negeri 3 Pematangsiantar, this result can be seen from the Tcount value of 33.60> Ttable 1.662, and it is concluded that Ho is rejected and Ha is accepted, meaning that the variables of teacher leadership and teacher communication skills have an influence on the motivation to learn economics of class XI students of SMA Negeri 3 Pematangsiantar. Then there is a joint or simultaneous influence between teacher leadership and teacher communication skills on the motivation to learn economics of class XI students of SMA Negeri 3 Pematangsiantar, seen from the Fcount value of 42.937> Ftable value of 3.104. The R Square determination coefficient test is known to be 0.9809, which means that 98% of the teacher leadership and communication skills variables influence the motivation to learn economics of class XI students of SMA Negeri 3 Pematangsiantar.